Religion, Sexuality, and Internalized Homonegativity: Confronting Cognitive Dissonance in the Abrahamic Religions - Meladze, Pikria (Journal of religion and health, 2015)
This research was aimed at investigating how religious beliefs and internalized shame predicted homonegativity. An online survey, which consisted of a self-report questionnaire assessing religious orientation, internalized shame, and internalized homonegativity, was completed by 133 Caucasian and Asian gay men. The respondents also were asked to write a short answer in which they had to explain how they integrated their religion and sexual practices. The quantitative analyses of data demonstrated no significant difference in internalized homonegativity among the two cultural groups. Internalized homonegativity was predicted by the main Abrahamic faiths (i.e. Christianity, Islam, and Judaism) and internalized shame. Qualitative analysis showed that gay men who adhere to a monotheistic religious faith follow a different path to reconciling their religion and homosexuality compared to gay men who adhere to Philosophical/New Age religions or to gay men who have no religious faith. The implications of these findings as well as directions for future research studies were discussed.